Visual axis pointing method and device of photoelectric pod and medium - GAO DEBIN; LI WENMING; ZHANG YINGPENG; WU WEI; ZHAO JIAXIN; LENG XUE; ZHAO DONGLONG (2023)
The invention particularly relates to a visual axis pointing method and equipment of a photoelectric pod and a medium. The method comprises the following steps: S1, establishing a rigorous imaging geometric model of the photoelectric pod; s2, obtaining an error equation according to the strict imaging geometric model; s3, calculating an initial value of a to-be-solved parameter of the error equation according to the approximate imaging model; s4, iteratively solving an azimuth frame angle alpha and a pitching frame angle beta; and S5, verifying the calculation result according to the scaling factor and the symbol of the positive image vector. Compared with an existing method, the visual axis can be aligned with the target more accurately, and especially for a photoelectric pod with a long focal length and a narrow field angle, the situation that the target is lost in the field due to large errors of visual axis pointing can be avoided. 本发明具体涉及一种光电吊舱的视轴指向方法、设备和介质。所述方法包括如下步骤：S1、建立光电吊舱的严密成像几何模型；S2、根据严密成像几何模型得到误差